Dynamical entrainment of corticospinal excitability during rhythmic movement observation: a Transcranial Magnetic Stimulation study. (7th May 2017) - Varlet, Manuel; Novembre, Giacomo; Keller, Peter E.
Abstract: Spontaneous modulations of corticospinal excitability during action observation have been interpreted as evidence for the activation of internal motor representations equivalent to the observed action. Alternatively or complementary to this perspective, growing evidence shows that motor activity during observation of rhythmic movements can be modulated by direct visuomotor couplings and dynamical entrainment. In‐phase and anti‐phase entrainment spontaneously occur, characterized by cyclic movements proceeding simultaneously in the same (in‐phase) or opposite (anti‐phase) direction. Here we investigate corticospinal excitability during the observation of vertical oscillations of an index finger using Transcranial Magnetic Stimulation (TMS). Motor‐evoked potentials (MEPs) were recorded from participants' flexor and extensor muscles of the right index finger, placed in either a maximal steady flexion or extension position, with stimulations delivered at maximal flexion, maximal extension or mid‐trajectory of the observed finger oscillations. Consistent with the occurrence of dynamical motor entrainment, increased and decreased MEP responses – suggesting the facilitation of stable in‐phase and anti‐phase relations but not an unstable 90° phase relation – were found in participants' flexors. Anti‐phase motor facilitation contrasts with the activation of internal motor representation as it involves activity in the motor system opposite from activity required for the execution of the observed movement. These findings demonstrate the relevance of dynamical entrainment theories and methods for understanding spontaneous motor activity in the brain during action observation and the mechanisms underpinning coordinated movements during social interaction. Abstract : Here we show the occurrence of dynamical entrainment of corticospinal excitability during action observation. Modulations of excitability occurred in the index finger flexor muscle (Flexor Digitorum Superficialis) while participants watched rhythmic movements of a model's index finger, which facilitated maximal flexion and extension towards in‐phase (movement in the same direction) but also anti‐phase (movement in opposite direction) relations.